THE LAW OF WORDS: STANDING, ENVIRONMENT, AND OTHER CONTESTED TERMS - Cassuto, David Nathan (Novos Estudos Jurídicos, 2018)
Friends of the Earth, Inc. v. Laidlaw Environmental Services (TOC), Inc., 528 U.S. 167 (2000), exposes fundamental incoherencies within environmental standing doctrine, even while it ostensibly makes standing easier to prove for plaintiffs in environmental citizen suits. According to Laidlaw, an environmental plaintiff needs only to show personal injury to satisfy Article ill’s standing requirement; she need not show that the alleged statutory violation actually harms the environment. This Article argues that Laidlaw’s distinbtion between injury to the plaintiff and harm to the environment is nonsensical. Both the majority and dissent in Laidlaw incorrectly assume that there exists an objective standard by which a plaintiff, society or a court can measure harm or injury. Using examples drawn both from history (the 7) aiI Smelter. Arbitration (1930-41)) and fiction (Barbara Klngsolver’s novel Animal Dreams), this Article illustrates that the inherent contingency of language renders it impossible to define harm or injury without acknowledging the systemic perspective from which the concepts are viewed. The path to an intelligible standing doctrine lies not in focusing on this artificial opposition, but instead in acknowledging statutory violations as injurious to the social and legal system of which we all form a part. Assuming the violated statute contains a citizen suit provision, the resulting harm to the system could and should enable individuals to sue. This policy would conform the Court’s standing jurisprudence to the language and intent of the statutes before Ii. Moreover, this policy would counter the undermining of the rhetoric of environmental protection that persists so long as the Supreme Court continues its frequent yet unsucceesfid efforts to retool its definition of cognizable legal injury.